In the Spirit of Kitchen Tables: A Conversation on Citation and Politics - Min-Venditti, Ame; Friedman, Leah M.; Najar Arevalo, Farah; Cruz, Lívia; Jenik, Adriene; Agloro, Alexandrina (KULA)

(untitled) (University of Victoria Libraries, 2026)
This piece unfolds as a multi-voiced dialogue among members of a co-lab who work as scholars, artists, dancers, professors, and storytellers and span diverse disciplinary homes including sustainability, art, science and technology studies, and life sciences. We position citation as a practice of community accountability, aesthetic expression, resistance to erasure, and care for knowledge lineages. We ask: Who are we accountable to when we cite? What does it mean to be in right relationship with our sources? How do citations enact care, reciprocity, and community? In our discussion of disciplinary and epistemological borders, we challenge academic conventions around what counts as knowledge and who counts as a knower, especially highlighting the need to cite Indigenous scholars not only when writing about Indigenous knowledge, but in honoring contemporary, place-based intellectual contributions. In our discussion on canon, we interrogate academic genealogies, metrics of influence, and the mechanisms by which expertise is legitimized. We propose alternate genealogies—such as "mother texts" and "grandmother texts"—and dream of visualizing non-traditional citation trees that encompass lived experience, artistic practice, and kinship with mentors, collaborators, and co-thinkers. Ultimately, this dialogue invites an expansive view of citation as world-building. Critically, this piece uses Chicago-style footnotes to engage with citational politics in dialogue and form: One of the co-authors engages with the dialogue post-hoc through the footnotes, and we use the footnotes to reveal the writing process and editorial review. Rather than merely naming sources, we reflect on what it means to be in conversation with them—across time, space, and medium. Through this piece, we aim to model a citational practice rooted in relational ethics, joy, complexity, and critique.